Characterization of Mechanical Property Degradation of Ion-Irradiated Materials - Mei, Luyao; Guo, Xun; Jin, Ke (Frontiers in Materials, 2022)
Evaluating the degradation of mechanical properties under irradiation is crucial for nuclear structural materials. Although ion irradiations have been commonly used for fundamental research on irradiation effects and fast screening of potential materials, the mechanical property tests on ion-irradiated materials are challenging due to the shallow irradiation depth. The research progress on utilizing small-scale mechanical property tests to characterize the ion-irradiation induced mechanical property degradation is the focus of this review. While the current techniques can access the mechanical properties at the nano- to micro-scale from various perspectives, the rationality and accuracy of the existing data analysis models, e.g., for the size-dependence, remain unclear or debating, especially for the ion-irradiated materials, resulting in the lack of consistency and reliability of the evaluation of the irradiation effects of materials. Establishing a standardized method is highly demanded to quantitatively bridge the gap between micro- and macro-scale mechanical properties of ion irradiated materials.